Allah speaks to the prophet musa - Khan, Saniyasnain (Goodword Kidz Place of publication not identified, 2004)
"Allah Speaks to the Prophet Musa" by Goodword recounts the profound moment when Allah communicates directly with Prophet Musa, emphasizing the significance of divine guidance and trust in God's commands. Through engaging storytelling, it highlights the themes of faith, obedience, and the power of revelation.